851 SMILE: Sustaining Medical Education in A Lockdown Environment. Student Perceptions of a Free Online Access Medical Education Platform as An Adjunct to The Traditional Undergraduate Curriculum During Lockdown. (4th May 2021) - Pascoe, J; Foster, P; Quddus, M; Kosti, A; Guest, F; Stevens, S; Bamford, R; Coulston, J
Abstract: Introduction: The coronavirus outbreak has had significant impact on medical students worldwide. SMILE is a free online access medical education (FOAMEd) platform. SMILE delivered 200 lectures during lockdown with up to 1400 students per session from UK medical schools and 33 abroad. Here we discuss student perceptions to SMILE during lockdown Method: A survey was used to collect information from students who had utilised the platform during lockdown. This examined access to learning, impact on mental health during lockdown and the differences between FOAMed and more traditional based campus lecture-based learning. Results: 1306 students responded to the survey. The majority of students were concerned regarding their training during lockdown, with 71% reporting an impact on their stress levels and 44% reporting a negative impact on mental health. On average students attended 4.3hours of teaching put on by their university per week, vs 7.9hours by SMILE. Positives included anonymity, making 80% more likely to both ask and answer questions, the informal approach, ease of access and enthusiastic teachers. Negatives included time differences and technical issues. Conclusions: Lockdown provided challenges in medical education, which platforms like SMILE addressed. Our experiences highlighted many positive outcomes of online medical education that may be applicable to other educators.